2-Dimensional Digital Animation Model for Public Health Socialization Assets - Ito Setiawan; Dhanar Intan Surya Saputra; Muhamad Faris Fakhrizal; Hellik Hermawan (Journal of Multimedia Trend and Technology, 2023)
Health is a very important aspect of human life. Human health will ensure that their lives continue to run well in everyday life in society. Currently, education about public health has been carried out in many ways by health agencies, from education by providing direct counseling to counseling using digital technology. However, not all health agencies have carried out health education through digital technology, one of which is the health agency at the Kaliwadas Community Health Center, where the agency has a problem where the staff at the agency have human data source competency and is still lacking competent in creating health education content for the public. This hampers public health education. The aim of this research is to create a digital content template to help simplify and speed up the production of health education content at the Kaliwadas Community Health Center. The method in this research uses the waterfall method which takes Sayanto as a reference, where this method consists of 3 stages, namely pre-production, production, and post-production.